The European electronic communications code: A critical appraisal with a focus on incentivizing investment in next generation broadband networks - Wolfgang Briglauer; Carlo Cambini; Thomas Fetzer; Kai Hüschelrath (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
In September 2016, the European Commission (EC) published its proposal for a directive establishing the European Electronic Communications Code (EECC) - with one key aim being the provision of sufficient incentives for infrastructure investments into high-speed communication networks. Based on a detailed review of the theoretical and empirical literature of the most relevant regulatory measures - that is, co-investment models as well as different types of access regulation - we provide a critical appraisal of the respective provisionsin the EECC. We find that, although the EECC can generally be seen as step into the right direction, the expected effects on investment incentives as well as substantial implementation challenges in combination with a high degree of complexity of the envisaged measures contain substantial potential for improvement.
urn:nbn:de:bsz:180-madoc-433680
Keywords: L96; L51; 330; Telecoms' Review; Regulatory Framework; European Union; Investment; Infrastructure; Next Generation Networks; Broadband; Access Regulation; Co-Investment